2020
DOI: 10.1002/prep.201900322
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Red Flare Pyrotechnic Compositions Modified with Gas Generating Additives

Abstract: In this work, an effective, but still not well‐explored area of red flare pyrotechnic formulations was investigated. High magnesium content (40–60 % w.t.) and the presence of conventional gas generating materials were the specific features of formulations explored herein. Such illuminant compositions possessed a low burning rate and high specific luminous intensity. The investigated system was based on strontium nitrate, rounded magnesium powder, chlorinated rubber, binder and gas generating additives. Emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Among the investigated additive materials, guanidinium nitrate (GN) showed the best performance to generate a high specific luminosity (Lsp). It found that the Lsp value is comparable to the total amount of oxygen and nitrogen present in the gas generating additive [19]. Further, blue color, with the wavelength ranging from 425 -500 nm, is commonly generated from copper based-compounds such as CuCO3.Cu(OH)2 [13], Cu powder electrolytic, basic copper carbonate Cu2(CO3)(OH)2, copper benzoate, Paris green, CuOCl, CuO [20] and Cu3Cl3 [21].…”
Section: Introductionmentioning
confidence: 99%
“…Among the investigated additive materials, guanidinium nitrate (GN) showed the best performance to generate a high specific luminosity (Lsp). It found that the Lsp value is comparable to the total amount of oxygen and nitrogen present in the gas generating additive [19]. Further, blue color, with the wavelength ranging from 425 -500 nm, is commonly generated from copper based-compounds such as CuCO3.Cu(OH)2 [13], Cu powder electrolytic, basic copper carbonate Cu2(CO3)(OH)2, copper benzoate, Paris green, CuOCl, CuO [20] and Cu3Cl3 [21].…”
Section: Introductionmentioning
confidence: 99%
“…It is imperative that the colour produced by the pyrotechnic powder should be easily distinguishable from this background colour that occurs primarily from the combustion of coal. While many different pyrotechnic flame colours such as red, [4][5][6][7][8][9][10] blue, [11][12][13][14][15][16][17][18][19] green, [9,[20][21][22][23][24][25][26][27][28][29] and a combination of these three are possible, green was selected as an easily identifiable colour, and formulations that emit green light were synthesized for this study.…”
Section: Introductionmentioning
confidence: 99%
“…These compositions were described as being not only cost-effective but also as having significant military and civilian applications. Red flare pyrotechnic compositions of high light intensity and color purity were obtained by Juknelevicius et al [3] using guanidinium nitrate as an additive component to classical mixtures. A study by Glück et al [4] showed that strontium nitrate can be successfully substituted by compounds of lithium as an effective, less environmentally polluting red colorant.…”
Section: Introductionmentioning
confidence: 99%